Acro-osteolysis and its relationship with bone mineral density and peripheral vascularity in premenopausal females with systemic sclerosis - Rabab S Zaghlol; Sahar S Khalil; Rania M Almolla; Ahmed Mohamed El-Maghraby; Wafaa K Makarm (Indian Journal of Rheumatology)
Objectives: To investigate the relationship between acro-osteolysis (AO), bone mineral density (BMD) and peripheral vascularity in premenopausal female patients with diffuse systemic sclerosis (dcSSc). Methods: An observational cohort study that included thirty premenopausal female patients with dcSSc. The recruited patients were categorized into two groups according to the presence of radiological signs of AO. Patients were assessed clinically, laboratory and radiologically by X-ray imaging of both hands and wrists, dual-energy X-ray absorptiometry for measuring BMD and Doppler ultrasonography for evaluation of upper limbs peripheral vascularity. Results: Overall, 80% patients had AO; comparing patients with and without AO, the former had significant increase in the frequencies of Raynaud's phenomenon, calcinosis and digital pits (88.5, 94.7, 91.7) versus (11.5, 5.3, 8.3) in the latter, respectively. Additionally, they had significantly lower distal radius BMD and higher macrovascular abnormalities at both radial and ulnar arteries ( P < 0.05). On regression analysis, the most important factors associated with AO were calcinosis (OR= 1.7; 95% CI: 1.01- 3.02; P = 0.02), Raynaud's phenomenon (OR= 3.5; 95% CI: 0.6-19.4; P = 0.003), digital pits (OR= 2.8; 95% CI: 0.9-8.8; P = 0.001), low BMD at the distal radius (OR= 1.9; 95% CI: 1.1-3.0; P = 0.002), and macrovascular changes at radial and ulnar arteries (OR = 2.2; 95% CI: 0.7-6.5; P = 0.04 and OR =1.6; 95% CI: 0.9-3.0; P = 0.05) respectively. Conclusion: Calcinosis, Raynaud's phenomenon, digital pits, vascular alterations at radial and ulnar arteries, and low BMD at the distal radius are the most important factors associated with AO in dcSSc patients.